MITOS DAN IDEOLOGI DALAM JEJAK KARYA PEPI AL-BAYQUNIE (Mith and Ideology in “Jejak” by Pepi Al-Bayqunie) - Uniawati, Uniawati (Balai Bahasa Sumatra Barat, 2017)
Mithical critic of a novel entitled “Jejak”, written by Pepi Al-Bayqunie was carried out to understand the mythology and ideology in the novel. Data used was text of the novel, which published by Pustaka Mafasa on 2015. The collection of data was done by reading intensively and making a basic narrative scheme in order to notice the plot of the story. The data was analyzed descriptively by using mythical critic theory. There were five steps as basic knowledge of mythical critic, (1) plot of the story, (2) characters and their ideology, (3) setting that represent the myth, (4) writer style of delivering the myth, and (5) the function of myth. The result showed the story if this novel through protagonist character represented two ideologiesin mythology, moderate, and conservative point of views. Setting at campus, community, and selection of characters showed the strong relationship toward the existence of mythology in the story. Mythology in this novel brought the benefits in building the characters and awarenessof the importance of a strong identity as a nation.